UAV-based field phenotyping based on low-cost, open-source hardware and software - Pereyra Irujo, Gustavo (2016)
Here we present a low-cost platform for field phenotyping based on an unmanned aerial vehicle (UAV), which consists mainly of free-to-use or open-source hardware and software. This platform consists of a multirotor helicopter -with 8 rotorsproviding great stability and maneuvrability, which is able to carry a variety of sensors for trait measurement. The platform is controlled by an electronic autopilot board, which can be programmed for GPS-guided, automatic flight through an open-source ground station software. This platform is currently equipped with a low-cost consumer camera modified for the acquisition of near infrared - green - blue images, thus allowing the capture of high-resolution vegetation index images. A pipeline for the processing, geo-referencing and analysis of the images has been developed, which is based on open-source and/or free-to-use software.